O contributo da ilustração na comunicação de questões sociais: sensibilização do público infantil através do álbum ilustrado - Santos, Pedro Emanuel (2018)
Illustrated albums cover a variety of topics, including some of sensitive themes, that is, relevant to humanistic formation. This project aims, through research and development of an illustrated book, to answer how the illustration can contribute to communicate a theme sensitive to the children's audience. The illustrated book in question is directed at children and has as its theme the violence, including domestic violence and ill-treatment. In order to understand if the use of the illustration can communicate to children the theme of violence, a practical analysis of its functioning is important. For this, was chosen the focus group methodology with a group of children, where it was verified that the message was transmitted and verified the importance that the illustrations had in this understanding, being possible to carry out the validation with priority actors of the objectives of this research project.